An empirical investigation of the relationship between organizational culture and organizational performance in a large public sector organization - Sawner, Thomas Edgar (ProQuest Dissertations & Theses, 2000)
This study investigates the relationship between organizational culture and organizational performance in a large military organization. Patterns of organizational culture are increasingly viewed as a critical factor for organizational success or failure and, as such, are the focus of a great deal of study (Frederiksen 1966; Angle and Perry 1981; Denison 1983; Wilkins and Ouchi 1983; Cameron 1985; Reynolds 1986; Krakower 1987; Safford 1988; Turnipseed 1988; Bettinger 1989; Byles, Aupperle et al. 1991; Calori and Sarnin 1991; Gordon and DiTomaso 1992; Lim 1995; Petty, Beadles et al. 1995; Coyler 1996). A key question, however, remains: Which patterns relate to success and which to failure? As part of his theory of action, Parsons (1960) identified four functions that are critical for long term organizational survival: adaptation, goal attainment, integration of activities and maintenance of the pattern of activities. Sashkin (1990) operationalized these functions as managing change, achieving goals, coordinating teamwork and building a strong shared culture. Additionally, Sashkin included a fifth scale as part of the goal-attainment function, a focus on customer satisfaction, now seen as important for effective goal-attainment. These operationalized functions form the basis of Sashkin's (1990) Organizational Culture Assessment Questionnaire (OCAQ) which was used to assess the culture of the subject organizations. Past studies (Denison 1990; Kotter and Heskett 1992; Coyler 1996) have examined and identified a variety of relationships between aspects of organizational culture and organizational performance. However, these studies focused on private sector organizations and financial measures were their primary indicator of organizational performance. This limits the generalizability of such results to the public sector. The present study provides a comprehensive assessment of the culture of a major public sector organization, the Air National Guard, and relates measures of organizational culture to a variety of non-fiscal performance measures. Based on the literature and previous research (Deal and Kennedy 1982; Denison 1990; Coyler 1996), it was hypothesized that organizational culture (as measured by the OCAQ) would have a statistically significant relationship with non-fiscal measures of organizational performance. The Air National Guard is composed of 88 individual “Wings.” A Wing is an organizational designation denoting a stand-alone unit of from 500 to 2500 personnel with a specific mission focus. For each Wing, the five cultural scales from the OCAQ, as well as the overall score, were correlated with the following set of performance measures: organizational inspection scores, personnel retention, and ground accident safety record. First, the correlations between culture and measures of performance for each Wing were determined. Then, a regression analysis was accomplished using the five OCAQ scores to predict performances measures (inspections scores, retention, and safety). Additionally, a factor analysis was performed on the OCAQ data. Overall, it was hypothesized that there would be statistically significant relationships between measures of culture and organizational performance. This hypothesis was generally proven correct by the results of the study.